Enhancement of InGaN Quantum Well Photoluminescence in a Tamm Metal/Porous-DBR Micro-Cavity - Andrei Sarua; Jon Pugh; Edmund Harbord; Martin Cryan (IEEE Photonics Journal, 2023)
Vertical cavity surface emitting lasers (VCSEL) are of great interest for photonic and telecom applications, however challenges in fabrication of efficient VSCEL GaN devices are yet to be resolved. In this work we present a study of micro-photoluminescence (PL) emission from a novel InGaN quantum well (QW) emitting structure with integrated micro-cavity, which can be used for VCSEL applications. The micro-cavity exhibiting Tamm plasmon optical states is formed by a porous GaN distributed Bragg reflector (DBR) bottom mirror and top plasmonic silver metal mirror. Results of PL, Fourier imaging spectroscopy and finite-difference time-domain simulations are presented and discussed. An estimated 8.5 times enhancement of QW PL intensity at around 480–500 nm and a red-shift of QW peak emission is attributed to the Tamm plasmon resonance in the cavity at around 514 nm.